Integration of MQTT and Node-RED for IoT-Based Server Room Temperature Monitoring System - Syahbana, Yoanda Alim; Jati, Aditya (ABEC Indonesia, 2024)
The absence of temperature monitoring in the server room of PT PLN (Persero) Unit Induk Distribusi Riauand Kepulauan Riau (UID RKR) poses a high risk to the stability of business processes at UID RKR. Without reliabletemperature monitoring, servers can experience overheating, potentially causing equipment damage and data loss. Thiswould result in disruptions to the electricity services provided by UID RKR. Based on these potential issues, this researchimplements an IoT device consisting of an ESP32 and a DHT22 temperature sensor connected to the Telegramapplication. The IoT device monitors the server room temperature in real-time and sends notification messages throughthe Telegram chatbot API if there is a drastic temperature change in the server room. The Information TechnologySystems Division (DSTI) of UID RKR can also send commands to the chatbot to obtain device status. Communicationbetween the IoT device and the chatbot is facilitated through the MQTT protocol. The integration of IoT devices, API,and the visual display of the monitoring system is developed using Node-RED, which strongly supports real-time dataprocessing. The monitoring system has been tested, including initial connection tests, temperature monitoringfunctionality, Telegram API message delivery, and system reliability. The test results show that the system has worked100% effectively and can reliably monitor the server room temperature 24/7 in real-time. Validation with DSTI has alsobeen conducted, and DSTI acknowledges the benefits provided by the monitoring system.